Implementasi Chatbot Kesehatan Kucing Melalui Dialogflow dan Telegram untuk Pemberian Informasi Penyakit dan Perawatan - Iqbal Dwi Haryanto; Saefurrahman Saefurrahman (Sekawan Institut, 2024)
Cats are an integral part of human life, but their health needs are often complicated for their owners. This research proposes and implements a Chatbot system using Natural Language Processing (NLP) through the Dialogflow framework to provide advice on cat care and treatment. This method is intended to help cat owners understand basic care needs and identify symptoms of illness their cat may be exhibiting. Using Dialogflow as the main framework enables intuitive and responsive interactions between chat owners and Chatbots. This system has gone through comprehensive stages of analysis, development and testing to ensure reliability and accuracy in providing cat health care information. This test also includes several real-life cases to validate the Chatbot's ability to provide appropriate treatment advice and solutions for cat health problems. The results of this research show that the application of Chatbots via Dialogflow has great potential in helping cat owners in caring for and dealing with diseases in cats. With the ability to understand natural language and provide accurate information, this Chatbot can be a useful tool to increase cat owners' understanding of proper care and early treatment of possible illnesses in their pets.